The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32819/019022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphogypsum on the chemical composition of aqueous extract from soil

Abstract: Crop irrigation on chernozems inappropriate to ecological requirements is often accompanied by degradation changes of soils: flooding, secondary salinization and soil alkalinity, destructurization, violation of gas regime, dehumidification, etc. Thus the necessity occurred to study comprehensively the changes in agroecological state of soils, having been irrigated with mineral water under conditions of the Northern Steppe of Ukraine. It has been proved that the irrigated soil solonization is a widespread negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Without irrigation, a better substitution of exchangeable sodium with calcium was observed in variants with the application of phosphogypsum at a dose calculated beyond the coagulation limit (6 tons per hectare). This aligns with previous studies [22,46,74].…”
Section: Discussionsupporting
confidence: 94%
“…Without irrigation, a better substitution of exchangeable sodium with calcium was observed in variants with the application of phosphogypsum at a dose calculated beyond the coagulation limit (6 tons per hectare). This aligns with previous studies [22,46,74].…”
Section: Discussionsupporting
confidence: 94%
“…As a result of long-term irrigation with water of different quality in the territory of the Northern Steppe of Ukraine, an acute problem of secondary salinization and salting of lands arose. A change in the natural state leads to the degradation of soils, their removal from their intended purpose due to the loss of fertility (Onopriienko et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This is explained by the arrival of SO 4 -2 ions with mineralized irrigation water and their content in phosphogypsum. The gradual decrease in the number of ions in the third year after the application of phosphogypsum is explained by the removal of the formed sodium sulfate into the lower soil horizons ( Onopriienko et al, 2019) During the research period, no corresponding dependence was observed in the change in amount of HCO 3 -1…”
Section: Source: Developed By Authorsmentioning
confidence: 91%
“…As a result of long-term irrigation with water of different quality in the territory of the Northern Steppe of Ukraine, an acute problem of secondary salinization and salting of lands arose. A change in the natural state leads to the degradation of soils, their removal from their intended purpose due to the loss of fertility (Onopriienko et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This is explained by the arrival of SO 4 -2 ions with mineralized irrigation water and their content in phosphogypsum. The gradual decrease in the number of ions in the third year after the application of phosphogypsum is explained by the removal of the formed sodium sulfate into the lower soil horizons ( Onopriienko et al, 2019) During the research period, no corresponding dependence was observed in the change in the amount of HCO 3 -1…”
Section: Source: Developed By Authorsmentioning
confidence: 91%